2006
DOI: 10.1002/pat.672
|View full text |Cite
|
Sign up to set email alerts
|

ArF excimer laser resists based on fluoroalcohol

Abstract: This paper reviews IBM's 193 nm resist development efforts, placing an emphasis on the systems employing fluoroalcohol as an acidic group. Polymethacrylates were initially selected as a platform for their good transparency at 193 nm and then the emphasis on dry etch resistance prompted the work on all‐norbornene systems. Carboxylic acid was employed in these resist systems as an acid group, which resulted in significant swelling during aqueous base development. Replacement of the carboxylic acid with fluoroalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In a previous work we did not observe improvement of adhesion of Cu films [26] and for this reason the use of complex amines (e.g. polydopamine [34][35][36][37][38][39][40][41]) as a buffer layer in deposition processes involving temperatures as high as 200°C is questionable.…”
Section: Introductionmentioning
confidence: 82%
“…In a previous work we did not observe improvement of adhesion of Cu films [26] and for this reason the use of complex amines (e.g. polydopamine [34][35][36][37][38][39][40][41]) as a buffer layer in deposition processes involving temperatures as high as 200°C is questionable.…”
Section: Introductionmentioning
confidence: 82%
“…13 In particular, we have developed a number of hexafluoroalcohol-based positive and negative tone resists for 193 nm lithography. [14][15] However, the combination of the moderately low pK a and the large amount of fluorine in the hexafluoroisopropanol structure also make fluoroalcohol-based methacrylate polymers very attractive for immersion topcoat materials. 16 Previously, we showed that minor structural changes in fluoroalcohol-based methacrylate copolymers can have large effects in both dissolution rate and receding contact angle.…”
Section: Introductionmentioning
confidence: 98%
“…Each method leads to its own polymer type, which is different in structure and properties from polymers made by the other two methods. Among these polymer types, vinyl-type polynorbornene (PNB) -which maintains its intact bicyclic structure in repeating units -has been considerably attracted because of its processibility and unique chemical and physical properties, such as excellent optical transparency, high thermal stability, high glass transition temperature (T g ), low moisture absorption, and low dielectric constant (k) [2,3]. These properties make the materials attractive for electronic and optical applications.…”
Section: Introductionmentioning
confidence: 99%